The new urban frontier gentrification and the revanchist city - Smith, Neil 1954-2012 (Routledge, 1996)
"Why have so many central and inner cities been radically revamped in the last three decades, converting urban decay into new chic? Will the process continue in the twenty-first century or has it ended? The New Urban Frontier challenges the conventional wisdom, which holds gentrification to be the simple outcome of changing middle-class tastes and a growing demand for urban living, and emphasizes instead gentrification as part of a much larger shift in the political economy and culture of the late twentieth century. Documenting in gritty detail the conflicts that gentrification brings to the new urban 'frontiers', Neil Smith explores the interconnections of urban policy, patterns of investment, eviction, and homelessness. The failure of liberal urban policy and the end of the 1980s' financial boom have made the end-of-the-century city a darker and more dangerous place. Public policy and the private market are conspiring against minorities, working people, the poor, and the homeless as never before. In the emerging revanchist city, gentrification has become part of this policy of revenge." http://www.loc.gov/catdir/enhancements/fy0649/95046015-d.html.
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Embourgeoisement (Urbanisme); Gentrification; Politique urbaine; Promotion résidentielle; Rénovation urbaine; Sociaal-economische verandering; Sociologie urbaine; Stedelijk beleid; Politik; Gentrification -- Government policy; Urban renewal; Urban policy; Kommunalpolitik; Gentrifizierung; USA